2022
DOI: 10.3390/ijms23020703
|View full text |Cite
|
Sign up to set email alerts
|

Altered Elemental Distribution in Male Rat Brain Tissue as a Predictor of Glioblastoma Multiforme Growth—Studies Using SR-XRF Microscopy

Abstract: Glioblastoma multiforme (GBM) is a particularly malignant primary brain tumor. Despite enormous advances in the surgical treatment of cancer, radio- and chemotherapy, the average survival of patients suffering from this cancer does not usually exceed several months. For obvious ethical reasons, the search and testing of the new drugs and therapies of GBM cannot be carried out on humans, and for this purpose, animal models of the disease are most often used. However, to assess the efficacy and safety of the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…noticed that the level of the element is higher within in the region of brain tumor comparing to the healthy tissue 98 . Similar observations were done during our previous study, analyzing brain samples taken from the area of glioma cells implantation 35 . The increased demand and accumulation of selenium in GBM tissue may be the cause of its low serum level.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…noticed that the level of the element is higher within in the region of brain tumor comparing to the healthy tissue 98 . Similar observations were done during our previous study, analyzing brain samples taken from the area of glioma cells implantation 35 . The increased demand and accumulation of selenium in GBM tissue may be the cause of its low serum level.…”
Section: Discussionsupporting
confidence: 82%
“…As it was shown in our earlier work 35 and one can see in the Figures S1 - S3 from the Appendix, after the implantation of T98G cells in the rat brain, no neoplastic tumor had developed. Despite this fact, in this study the animals from group T showed a number of elemental anomalies in the examined organs.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Planeta and colleagues applied X-ray fluorescence microscopy based on synchrotron radiation to study the micro changes of the rat brain in which HGG develops [103] (Figure 10A) (Table 2). The changes in the animal brain implanted with two different stabilized lines of human HGG and with an HGG (GB) taken directly from a patient were compared.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Orthotopic rat models of GB. [103] LAT1 as a new marker for GICs. LAT1+ and LAT1-glioma cells sorted by flow cytometry.…”
Section: Major Findingmentioning
confidence: 99%